The Effect of Entrepreneurial Characteristics on Entrepreneurial Competence and Entrepreneurial Competence on Business Performance of Micro and Small-Scale Coffee Shops in Bogor - Muhammad Reza Aulia; Cyprianus PH Saragi; Ramses Simbolon (Universitas Muhammadiyah Jakarta, 2021)
This research aims to analyze the influence of entrepreneurial characteristics towards entrepreneurial competencies and entrepreneurial competencies towards the business performance of micro and small scale coffee shops in Bogor. In this research, entrepreneurial characteristics consist of individual and psychological characteristics; which individual characteristics were reflected by age, education, experience, cosmopolitan; psychological characteristics reflected by motivation and need of achievement; entrepreneurial competencies reflected by managerial skill, conceptual skill, social skill, decision making skill and time managerial skill; business performance reflected by profit and sales volume. This research used 60 data samples of coffee shops consisting of 30 unit micro scale and 30 unit small scale coffee shops that were collected through random sampling in Bogor from February 2018 until June 2018. The data were analyzed by SEM-PLS analysis with SMART PLS 3 software. The result showed that entrepreneurial competencies in small scale model were influenced by individual characteristics and psychological characteristics whereas entrepreneurial competencies in micro scale model were only influenced by individual characteristics. The business performance was influenced by entrepreneurial competencies both in micro scale model and small scale model.